2010
DOI: 10.1016/j.envpol.2009.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Bioanalytical characterisation of multiple endocrine- and dioxin-like activities in sediments from reference and impacted small rivers

Abstract: A comprehensive evaluation of organic contamination was performed in sediments sampled in two reference and three impacted small streams where endocrine disruptive (ED) effects in fish have been evidenced. The approach combined quantitative chemical analyses of more than 50 ED chemicals (EDCs) and a battery of in vitro bioassays allowing the quantification of receptor-mediated activities, namely estrogen (ER), androgen (AR), dioxin (AhR) and pregnane X (PXR) receptors. At the most impacted sites, chemical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 42 publications
4
64
0
1
Order By: Relevance
“…However, most organic chemicals could be metabolized by cultured cells after 72 h of incubation (Jones et al, 2000;Kinani et al, 2010). Therefore, the EROD activity after 72 h of incubation is mainly caused by more persistent AhR agonists, and that EROD activity after 24 h of incubation is defined as the total AhR potency of the mixture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most organic chemicals could be metabolized by cultured cells after 72 h of incubation (Jones et al, 2000;Kinani et al, 2010). Therefore, the EROD activity after 72 h of incubation is mainly caused by more persistent AhR agonists, and that EROD activity after 24 h of incubation is defined as the total AhR potency of the mixture.…”
Section: Discussionmentioning
confidence: 99%
“…The EROD induction of a sample after 24 h and 72 h of incubation with the cultured cells was measured with a fluorescence reader. Since most organic chemicals can be metabolized by cultured cells after 72 h of incubation (Jones et al, 2000;Kinani et al, 2010), the induction caused by sample extracts after 72 h of incubation is mainly caused by more persistent AhR agonists while the induction after 24 h of incubation is defined as total AhR activity. Co-exposure experiment with TCDD standard was performed to test potential non-additive effects in samples.…”
Section: Introductionmentioning
confidence: 99%
“…The EROD induction caused by sample extracts after 24 h of incubation (total AhR agonists) ranged from 200 to 311 pg TCDD EQ g −1 dw, and after 72 h of incubation (more persistent AhR agonists), it ranged from 45 to 76 pg TCDD EQ g −1 dw. Because most organic chemicals could be metabolized by cultured cells after 72 h of incubation (Jones et al 2000;Kinani et al 2010), the EROD activity after 72-h incubation is mainly caused by more persistent AhR agonists and that after 24-h incubation is defined as the total potency of the mixture of AhR agonists. The results showed that more persistent AhR agonists accounted for 18 to 37 % of the total AhR agonists.…”
Section: Erod Activity Of Samplesmentioning
confidence: 99%
“…Due to this physiological property, the stickleback is considered as a relevant model fish species to assess the (anti)androgenic effects of endocrine-disrupting chemicals (EDCs) in laboratory and field studies (Sanchez et al 2008b;Katsiadaki et al 2006;Pettersson et al 2007;Wartman et al 2009). Chemical analysis has led to the identification of chemicals involved in this biological activity and showed that natural androgenic compounds such as androstenedione, equol, dehydrotestosterone or androsterone represent a large part of measured activity (Hill et al 2010;Thomas et al 2002;Kinani et al 2009). Field studies have described physiological changes associated with androgen exposure such as spiggin induction in stickleback from contaminated sites (Sanchez et al 2008b;Katsiadaki et al 2006;Pettersson et al 2007;Wartman et al 2009) or elongated anal fin rays, resembling the male gonopodium, in female mosquitofish (Gambusia sp.)…”
Section: Introductionmentioning
confidence: 99%